The Relationship Between Screen Time, Sleep and Obesity - Lewandowska, Dominika; Rosińska-Lewandoska, Dominika; Podraza, Zofia; Strep, Dominika; Grabowska, Julia; Rosiński, Jakub; Głowniak, Zofia; Kwiatkowski, Maciej; Kwiatkowska, Izabela; Soja, Malwina (Journal of Education, Health and Sport, 2025)
Introduction Excessive screen time has emerged as a major public health concern, particularly due to its association with sleep disturbances and the rising prevalence of obesity. Digital technologies have become deeply integrated into daily life, leading to prolonged exposure to screens and subsequent health challenges. This review explores the intricate relationships between screen time, sleep, and obesity, focusing on underlying behavioral, hormonal, and psychological mechanisms, as well as potential interventions to address these interconnected issues. Materials and Methods A systematic review of 35 peer-reviewed studies published between 2019 and 2025 was conducted. Sources were identified using PubMed, focusing on studies examining the interplay of screen time, sleep quality, and obesity. Inclusion criteria included studies on children, adolescents, and adults, ensuring a comprehensive understanding of these relationships across age groups. Analysis of the Literature The review investigates three main aspects: the impact of screen time on sleep quality, the bidirectional relationship between sleep disturbances and obesity, and how excessive screen time contributes to energy imbalance and weight gain. Mechanistic pathways such as altered circadian rhythms, sedentary behaviors, and exposure to food advertising are also explored. Conclusions Screen time significantly affects sleep and obesity through behavioral, hormonal, and psychological pathways. Interventions targeting reduced screen exposure, improved sleep hygiene, and increased physical activity could mitigate obesity risk, especially in vulnerable populations such as children and adolescents. Public health strategies and educational campaigns are essential to raise awareness and promote healthier screen habits. Future research should focus on longitudinal studies and scalable